ALUMINIUM OXIDE (Al2O3)-FEW LAYER GRAPHENE (FLG) REINFORCED ALUMINIUM HYBRID COMPOSITES - Kaykilarli, Cantekin; Altinisik, Zehra; Kilic, E. Can; Uzunsoy, Deniz; Yeprem, H. Aygul (POLISH SOC COMPOSITE MATERIALS, 2022)
The present study investigates the microstructural and mechanical properties of few layer graphene (FLG, 0.1 to 5 wt.%) and aluminium oxide (Al2O3, 4 to 20 wt.%) reinforced Al6061 matrix composites prepared via mechanical alloying (MA), uniaxial pressing and pressureless sintering. The effects of the amounts of Al2O3 and FLG were studied. MA was carried out at 300 rpm for 3 h in a planetary ball mill in argon atmosphere. The mechanically alloyed (MAed) powders were compacted via uniaxial pressing (400 MPa) and sintering (620 degrees C, 2 h). The microstructural and mechanical properties of the Al-xAl(2)O(3)-yFLG powders and bulk samples were investigated via X-ray diffraction (XRD), light microscopy (LM), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), the Archimedes' method and a hardness test. In the XRD analysis, the aluminium carbide (Al4C3) phase was not detected. The SEM, LM micrographs and EDS results show that the produced composites have a homogeneous structure. Based on the Archimedes' method, the densification rates of the rein-forced samples were higher than the unreinforced sample. The Al-20Al(2)O(3)-3FLG sample exhibited the highest relative density, 99.25%. According to the hardness measurements, the highest hardness value was 87.28 HV for the Al-20Al(2)O(3)-1FLG composite and increased twofold compared to Al6061.
Keywords: Al matrix composites; Al6061; aluminium oxide; few -layer graphene; powder metallurgy; hardness; MECHANICAL-PROPERTIES; TRIBOLOGICAL BEHAVIOR; WEAR BEHAVIOR; MICROSTRUCTURE; Materials Science